FAKTOR YANG MEMPENGARUHI KADAR KOLINESTERASE DALAM DARAH PADA BURUH TANI - Indah Tawakkalni; Winarko .; Nur Haidah (GEMA LINGKUNGAN KESEHATAN, 2019)
Pesticides in the agricultural sphere play an important role in controlling pests and weeds to protect agricultural products. Pesticides are toxic and dangerous materials, which can cause poisoning and environmental damage. This study aims to determine the effect of pesticide poisoning on farm workers.This study is an observational study that is analytical in nature using a cross sectional approach. The location used in this study was conducted in Takerharjo Village, Solokuro District, Lamongan Regency. The sample size in this study was 40 people who used pesticides and were willing to take blood. Data were collected through interviews and laboratory examinations and then processed and analyzed using the Fisher's exact test with the help of the SPSS statistical program.The results of the examination of cholinesterase levels in the blood of farm workers showed that 92.5% were normal or did not experience pesticide poisoning. The results of the Fisher's exact test showed that there was an influence on the level of knowledge of pesticide poisoning and there was an effect of using personal protective equipment on pesticide poisoning, whereas for other variables there was no effect on pesticide poisoning which included dosage use, spraying time, spraying frequency, working period.Suggestions for the community to hold discussions or outreach, use complete personal protective equipment, use the right dosage of pesticides, improve self-safety against symptoms of poisoning, hold periodic petroleum health checks, improve supervision of the use of pesticidesand need to do further research on other factors affect pesticide poisoning. Keywords: Factors, Pesticide, Poisoning, Farmer Labor